Real-world clinical and cost analysis of CT coronary angiography and CT coronary angiography-derived fractional flow reserve (FFRCT)-guided care in the National Health Service. Issue 11 (November 2021) - Graby, J.; Metters, R.; Kandan, S.R.; McKenzie, D.; Lowe, R.; Carson, K.; Hudson, B.J.; Rodrigues, J.C.L.
Abstract : AIM: To quantify the real-world clinical and cost impact of computed tomography (CT) coronary angiography (CTCA)-derived fractional flow reserve (FFRCT ) in the National Health Service (NHS). MATERIALS AND METHODS: Consecutive clinical CTCA examinations from September to December 2018 with ≥1 stenosis of ≥25% underwent FFRCT analysis. The Heart Team reviewed clinical data and CTCA findings, blinded to FFRCT values, and documented hypothetical consensus management. FFRCT results were then unblinded and hypothetical consensus management re-recorded. Diagnostic waiting times for management pathways were estimated. A per-patient cost analysis for diagnostic certainty regarding coronary artery disease (CAD) management was performed using 2014–2020 NHS tariffs for pre- and post-FFRCT pathways. RESULTS: Two hundred and fifty-one CTCAs were performed during the study period. Fifty-seven percent (145/251) had no CAD or stenosis <25%. One study was non-diagnostic. Of the remaining 42% (105/251), two were ineligible for FFRCT and there was a 5% (5/103) failure rate. FFRCT led to a change in hypothetical management in 65% (64/98; p< 0.001) patients with a functional imaging test cancelled in 17% (17/98) and a diagnostic angiogram cancelled in 47% (46/98). FFRCT -guided management had a reduced mean time to definitive investigation compared with CTCA alone (28 ± 4 versus 44 ± 4 days; p= 0.004). Using the proposed 2020/21 tariff, CTCA + FFRCT for stenosis ≥50% resulted in a diagnostic pathway £44.97 more expensive per patient than usual care without FFRCT . CONCLUSIONS: In the real-world NHS setting, FFRCT -guided management has the potential to rationalise patient management, accelerate diagnostic pathways, and depending on the stenosis severity modelled, may be cost-effective. Highlights: FFRCT changed management in 65% of patients in a real-world NHS DGH population. FFRCT did not appear to significantly alter management on a per patient basis for stenoses <50%. FFRCT assessment of stenoses ≥50% may be the most cost-effective pathway.